Prevalence of Caries with its Distribution by Age & Gender in Institutional Clinical Patients (Medicine Today, 2023)
Introduction: Consequence of dental caries is loose of healthy tooth structure which impacts negatively on aesthetics, function, self-esteem and quality of life of the patients. Different age groups and populations exhibit distinct caries prevalence rates, observations of which could provide a useful descriptive measure of caries susceptibility in tooth surfaces.Materials and Methods: In this study, patients attending the Department of Conservative Dentistry & Endodontics of Dhaka Dental College & Hospital, located in Mirpur-14 and Department of Conservative Dentistry & Endodontics of Sapporo Dental College & Hospital, located in Abdullahpur (North Dhaka City), Bangladesh, were examined between 2017 and 2019. The location of dental caries on the teeth surfaces was recorded as following surface: Occlusal , Mesio-occlusal, Disto-occlusal, Proximal and Cervical for statistical evaluation and comparison. Furthermore, the age and gender of the patients were recorded on the chart for each caries tooth. Result: Female had higher incidence 86 (57%) of caries than males 64 (43%). Caries distribution was common in the maxillary jaw (53.38%) than in the mandibular jaw (46.62%). Among our study patient occlusoal surface caries was most commonly observed (43.4%). Then, the proximal surface caries was seen in 28.3% cases. Overall 71.7% prevalence of caries was in occlusal and proximal area. Where, prevalence of proximal and cervical surface caries was higher in maxillary tooth (18.9% and 4.82%) than mandibular tooth (9.3% and 2.6%) respectively. Conclusion:  Female are more prevalent to dental caries than male. Occlusoal surface caries is most commonly observed, then, the proximal surface caries are commonly seen. Occlusal surface caries is more common in mandibular tooth than maxillary. Where, proximal and cervical surface caries was higher in maxillary tooth.  Medicine Today 2023 Vol.35(2): 78-82